Pengelolaan Dana Zakat produktif untuk Kesejahteraan Mustahik Melalui Program Solok Sejahtera (Studi pada BAZNAS Kota Solok) - Emrizal Emrizal; Ahmad Muzaki (ZAWA: Management of Zakat and Waqf Journal, 2023)
BAZNAS Solok City uses program management, namely zakat received by officers from Muzakis is collected and managed to later be distributed to recipients of productive zakat funds while the mechanism for selecting and determining the criteria for receiving Solok Sejahtera program assistance, namely through the Solok City BAZNAS program, can be determined thoroughly through the fulfillment of 7 criteria in the SOP for the distribution of productive Zakat assistance in the Solok Program Prosperous. Meanwhile, the contribution of BAZNAS Solok Sejahtera City in Improving Mustahik Welfare, namely a. As a Productive Zakat Manager through the management of zakat for zakat aid recipients, mustahik prepares a requirement file which will later be submitted to the field of collection and distribution. b. As a Distributor of Zakat funds. The Solok Sejahtera program itself has 4 divisions, namely: (Individual Business Capital, Group Business Capital, Continue Business Capital, Business Capital. c. As a coach, BAZNAS Solok City conducts sustainable coaching.